Synthesis of Ethylene Glycol from Ethylene - Battalgazy, Bekassyl; Mazhit, Birzhan; Shildebayev, Temirlan; Zhanbassynova, Ainur; Akhmetov, Zhanibek (Nazarbayev University School of Engineering and Digital Sciences, 2020)
This capstone report focuses on production of ethylene glycol from ethylene. This work is a continuation of Capstone I project, where the analysis of raw materials and final products, market analysis, feasibility study and analysis of global manufacturers was conducted, as well as ethylene glycol possible production pathways were evaluated, and site location was selected. In scope of this work, Shell OMEGA process was found to be economical in terms of product requirements and energy consumption, satisfying the desired yield of production and relatively easy catalyst separation from the product. The OMEGA process subsumes three reaction steps such as oxidation of ethylene in the presence of silver catalyst and chlorine moderator which helps to avoid over-oxidation, carbonation of ethylene oxide and hydrolysis of ethylene carbonate. The resulting product is dehydrated and purified from other by-products. According to economic research done in this work, it was decided to state the production rate as 100 kT ethylene glycol per year. The reaction kinetics and thermodynamic models for each step of reaction are discussed and validated. To design main units of the process Aspen Plus software was used. To reach the desired rate of ethylene glycol production, process optimization was made. Overall, this research and design work conducted for design of pure ethylene glycol production plant can be considered as a preliminary plan for the plant design in practical industrial conditions.
Keywords: Ethylene; Synthesis; Ethylene Glycol; Research Subject Categories::TECHNOLOGY; oxidation of ethylene